2022
DOI: 10.1002/ejhf.2419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sacubitril/valsartan on investigator‐reported ventricular arrhythmias in PARADIGM‐HF

Abstract: Sudden death is a leading cause of mortality in heart failure with reduced ejection fraction (HFrEF). In PARADIGM-HF, sacubitril/valsartan reduced the incidence of sudden death. The purpose of this post hoc study was to analyse the effect of sacubitril/valsartan, compared to enalapril, on the incidence of ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…A post‐hoc analysis of the Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure (PARADIGM‐HF) trial analysed the effects of sacubitril/valsartan, compared to enalapril, on the incidence of ventricular arrhythmias. Sacubitril/valsartan reduced the risk of ventricular arrhythmias, as well as the composite of ventricular arrhythmia, implantable cardioverter defibrillator shock or resuscitated cardiac arrest, especially in patients with an ischaemic aetiology 36 …”
Section: Guideline‐directed Medical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A post‐hoc analysis of the Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure (PARADIGM‐HF) trial analysed the effects of sacubitril/valsartan, compared to enalapril, on the incidence of ventricular arrhythmias. Sacubitril/valsartan reduced the risk of ventricular arrhythmias, as well as the composite of ventricular arrhythmia, implantable cardioverter defibrillator shock or resuscitated cardiac arrest, especially in patients with an ischaemic aetiology 36 …”
Section: Guideline‐directed Medical Therapymentioning
confidence: 99%
“…Sacubitril/valsartan reduced the risk of ventricular arrhythmias, as well as the composite of ventricular arrhythmia, implantable cardioverter defibrillator shock or resuscitated cardiac arrest, especially in patients with an ischaemic aetiology. 36…”
Section: Guideline-directed Medical Therapymentioning
confidence: 99%
“…Should it not be that the non‐use of such strongly preventative medications be considered a precipitant of subsequent HF hospitalization? Likewise, among the effects of these medications are reductions in arrhythmias, 13 prevention of worsening kidney function, 14 and lowering of blood pressure, 15 benefits which directly address many of the worsening HF precipitants perceived by investigators in REPORT‐HF. Thus, while perturbations in haemodynamics and renal function certainly require urgent attention when patients present with worsening HFrEF, it may be important to consider absence of comprehensive disease‐modifying medical therapy as the frequent root cause of the clinical deterioration.…”
Section: Prevention Of Worsening Chronic Heart Failurementioning
confidence: 99%
“…Kawashima [ 3 ] showed that there was a significant interaction in mortality between treatment effect (percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG)) and the presence or absence of heavily calcified lesions (HCLs) (P interaction = 0.005). Another study [ 4 ] estimated the risk of death related to ventricular arrhythmia in time-updated models. This study examined the interaction between heart failure etiology and the effect of sacubitril/valsartan.…”
Section: Introductionmentioning
confidence: 99%